PROSES PEMBUATAN SPROCKET DI PT. AMANAH JAYA PERSADA MAJALENGKA - Muhammad Setiyo Surya Darma; Koswara, Engkos (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The process of making sprockets using a lathe begins with rolling a suitable raw material, such as steel or another metal alloy. The raw material is then installed on the lathe machine table and clamped tightly. After that, the lathe knife is placed near the workpiece and regularly moved in the specified direction, cutting off excess material until it reaches the desired shape and size. Operating a lathe requires a skilled operator to produce sprockets with tight tolerances. The purpose of writing a practical work report at PT. Amanah Jaya Persada is to know the process of making sprockets and know the lathe and CNC processes in making sprockets. The conclusion from this research is that there are 4 processes for making sprockets at PT. Amanah Jaya Persada, namely making drawings using Solidwork, forming shaft holes using a lathe, forming chamfers using a lathe, forming a chain release (Undercut) using a lathe, and forming sprocket teeth using a CNC milling machine.